IMPLEMENTASI KEBIJAKAN PENETAPAN PAJAK KENDARAAN BERMOTOR PADA KANTOR BERSAMA SAMSAT AMURANG MINAHASA SELATAN - SOPUTAN, INDRIANI; LONDA, VERY; PALAR, NOVIE (JURNAL ADMINISTRASI PUBLIK, 2021)
This study aims to explain the implementation of the motor vehicle tax determination policy at the samsat amurang minahasa selatan joint office. This research uses qualitative research, and data collection techniques are carried out by means of literature, observation, interviews and documentation. The theory of the approach used is based on 4 indicators as follows (i) communication, (ii) resources, (iii) the attitude of the executor, (iv) the bureaucratic structure of the organization. The results of this study indicate that the implementation of the motor vehicle tax determination policy at the samsat amurang minahasa selatan joint office is carried out well in terms of communication, resources, executive attitudes, bureaucratic structure and organization. To further improve the principle of implementing the motor vehicle tax determination policy at the south minahasa samsat amurang joint office, it is hoped that the officers will improve their performance again in order to achieve an effective and efficient performance towards services. Keywords : implementation, policy, determination, tax, vehicle, motor.